THE USE OF MINERALOCORTICOID RECEPTOR ANTAGONISTS IN THE PRE VENTION OF ATRIAL FIBRILLATION - N. T. Vatutin; A. N. Shevelok; G. G. Taradin; I. N. Kravchenko (SINAPS LLC, 2019)
Atrial fibrillation (AF) is one of the most common cardiac rhythm disorders. Its prevalence is about 1 % in the general population and exceeds 7 % in individuals older than 60 years of age. It is known that hyperactivation of the renin-angiotensin-aldosterone system plays a key role in structural and electrical myocardial remodeling in AF. Increased activity of the renin-angiotensin-aldosterone system causes inflammation, fibrosis and oxidative stress in cardiomyocytes. Last studies suggest that most of negative effects previously explained by angiotensin-2 may be particularly caused by excessive aldosterone activity. More data about extra-adrenal hormone production (in the myocardium, the vascular wall and even the brain) have appeared, and its receptors were found far beyond the kidneys - in cardiomyocytes, endothelial cells, fibroblasts, monocytes, and macrophages. It was also shown that aldosterone has a wide profile of pathogenic effects, one of which is the stimulation of atrial myocardial fibrosis as the structural basis for AF. The discovery of new features of aldosterone suggests that blockade of mineralocorticoid receptors may prevent or slow down atrial remodeling and thereby reduce the incidence of AF. The article presents data of the world literature and the results of own studies devoted to the use of mineralocorticoid receptor antagonists in patients with AF. Modern concepts of the role of aldosterone in the arrhythmia development and the main approaches of upstream-therapy are described. The possibilities of using eplerenone and spironolactone in primary and secondary prevention of AF are discussed.